Niobium incorporated WO 3 nanotriangles: Band edge insights and improved photoelectrochemical water splitting activity - Kalanur, Shankara S.; Yoo, Il Han; Cho, In Sun; Seo, Hyungtak (Ceramics International, 2019)
In this work, a facile hydrothermal method is proposed to fabricate Nb-doped WO 3 nanotriangle thin films, and their band edge properties and photoelectrochemical water splitting activity were explored. The process of doping and thin film formation was simultaneously achieved in a single step hydrothermal condensation of peroxopolytungstic acid solution containing Nb precursor. The crystallographic study reveals that doping of Nb into WO 3 lattice obstructs the reconstructive transformation of orthorhombic WO 3 ·0.33H 2 O during annealing consequently producing hexagonal phase instead of the monoclinic phase. The insertion of Nb causes the increase in band gap and induces oxygen vacancies in WO 3 . Uniform distribution of Nb in WO 3 was observed containing majorly Nb 5+ valence and a small amount of Nb 4+ state. PEC characterization showed the increase in photocurrent, (at AM 1.5G illumination) incident photon to current and photoconversion efficiency values of WO 3 upon Nb doping. Band edge analysis revealed that both conduction and valence band edge of WO 3 show downward shift towards higher potential vs. RHE whereas the Fermi level show upward shift as a result of Nb doping.
Keywords: Band edge; Crystallographic studies; Peroxopolytungstic acid; Photoconversion efficiency; Photoelectrochemical water splitting; Reconstructive transformation; Tungsten oxide; Uniform distribution; Band edge; Niobium; Photoelectrochemical water splitting; Reconstructive transformation; Tungsten oxide